PML Nuclear Bodies and Cellular Senescence: A Comparative Study of Healthy and Premature Aging Syndrome Donors’ Cells - Eugene Y. Smirnov; Sergey A. Silonov; Eva A. Shmidt; Aleksandra V. Nozdracheva; Nadezhda M. Pleskach; Mirya L. Kuranova; Anastasia A. Gavrilova; Anna E. Romanovich; Irina M. Kuznetsova; Konstantin K. Turoverov; Alexander V. Fonin (Cells)
Natural aging and age-related diseases involve the acceleration of replicative aging, or senescence. Multiple proteins are known to participate in these processes, including the promyelocytic leukemia (PML) protein, which serves as a core component of nuclear-membrane-less organelles known as PML nuclear bodies (PML-NBs). In this work, morphological changes in PML-NBs and alterations in PML protein localization at the transition of primary fibroblasts to a replicative senescent state were studied by immunofluorescence. The fibroblasts were obtained from both healthy donors and donors with premature aging syndromes (ataxia-telangiectasia and Cockayne syndrome). Our data showed an increase in both the size and the number of PML-NBs, along with nuclear enlargement in senescent cells, suggesting these changes could serve as potential cellular aging markers. Bioinformatic analysis demonstrated that 30% of the proteins in the PML interactome and ~45% of the proteins in the PML-NB predicted proteome are directly associated with senescence and aging processes. These proteins are hypothesized to participate in post-translational modifications and protein sequestration within PML-NBs, thereby influencing transcription factor regulation, DNA damage response, and negative regulation of apoptosis. The findings confirm the significant role of PML-NBs in cellular aging processes and open new avenues for investigating senescence mechanisms and age-associated diseases.